SANGZOR BASIN NATURE AND HIM PROTECTION TO DO MECHANISMS - D. Akhmedova (European International Journal of Pedagogics, 2023)
In the article, Sangzor basin nature to himself special features , color and to them effect doer factors studied and analysis done.